Repetitive transcranial magnetic stimulation as a modality of treatment in patients with fibromyalgia - Rawan M. El Shahat; Mona A. El Sebaie; Sahar F. Ahmed; Shereen I. Fawaz; Marwa A. Kamel; Marwa A. Nassef (Egyptian Rheumatology and Rehabilitation)
Abstract Background Fibromyalgia is characterized by widespread musculoskeletal pain and tenderness. It is also frequently associated with mood disorders, tiredness, sleep disturbances, and cognitive dysfunction. Repetitive transcranial magnetic stimulation (rTMS) is an emerging nonpharmacological therapeutic option for fibromyalgia. rTMS involves an electromagnetic coil placed on the scalp that is rapidly turned on and off to generate short magnetic pulses to the brain (2). rTMS can reduce chronic pain by triggering inhibitory neural pathways at the level of the dorsal horn of the spinal cord. It can improve motor function and alleviate psychiatric symptoms, including depression and anxiety, in many diseases (7). Aim of the work The study aimed to evaluate the role of repetitive transcranial magnetic stimulation (rTMS) in treating fibromyalgia. Results Highly significant improvement in feel-good and work-missed scores by FIQ being lower in the case group compared to the control group (p-values 0.008 and 0.003 respectively). On comparing the control and case groups regarding anxiety and depression using the HADS questionnaire and fatigue assessment using the SF36 questionnaire after rTMS sessions, there was a statistically significant lower depression score in the case group compared to the control group (p-value of 0.024), and statistically significant higher energy/fatigue scores in the case group compared to the control group with (p-value = 0.004). Conclusion This study demonstrated that rTMS relieved pain, reduced anxiety, depression, and fatigue and enhanced quality of life in patients with fibromyalgia.